The relationship of exports, imports and economic growth between China and selected Asean countries - Li, Ying Xian (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study examines the relationship between the exports, imports and economic growth among China and the five selected ASEAN countries over the period of year 1993 to 2010. The annual time series data are collected from the Asian Development Bank and World Data Bank statistic databases in 2011. The variables used are includes the exports, imports, and GDP growth rate. The estimation methods of the study includes the Dickey Fuller Generalized Least Squares (DF-GLS) Unit Root Tests, Autoregressive Distributed Lag (ARDL) bound test, Error correction representation for ARDL model, and the Granger causality test. The empirical results show that the exports and imports between China and the five selected ASEAN countries contribute to the economic growth for those selected ASEAN countries which are Philippines, Vietnam, Indonesia, Thailand and Malaysia.